Stability analysis of rectangular plates - Mendoza, Alberto B. (1977)
A finite element approach on the buckling analysis of rectangular plate is presented here with an accompanying through matrix formulation as well as detailed algorithm for the solution of the Eigenvalue problem. The following were analyzed in this paper: 1. Square plate is simply supported on all edges and 2. Square plate with fixed support on all edges loaded under a. Uniform compression load on one direction b. Uniform biaxial loads on both direction Results obtained in comparison with theoretical values and finite difference method were generally very good.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Keywords: Elastic plates and shells; Elastic analysis (Theory of structures).